The Influence of Service Quality and Station Facilities on Mass Rapid Transit Jakarta Passengers' Satisfaction - Prasidi, Abi; Fachrial, Peppy; Fitri Sabilla, Mutiara; Maisarah, Putri; Ratnasari, Devi; Pahrudin, Cecep (KnE Social Sciences, 2023)
Mass Rapid Transit (MRT) is an effective and convenient electric rail-based transportation system which has proven to have positive results since it is applied in large cities in various countries. Various facilities at MRT stations are provided to facilitate customer service. This study aimed to determine the effect of service quality and station facilities on user satisfaction when using the Jakarta MRT. The research method used was quantitative research using a questionnaire. The sample was 100 respondents from MRT user data using the Slovin Formula. The results indicated that the quality of service and station facilities has an influence of 52.7% and strongly relates to user satisfaction. Keywords: Service Quality, Facilities, Passenger Satisfaction